2020
DOI: 10.3389/fpsyg.2020.00402
|View full text |Cite
|
Sign up to set email alerts
|

Feeling at Home in the Wilderness: Environmental Conditions, Well-Being and Aesthetic Experience

Abstract: Environmental conditions affect one's aesthetic experience in natural environments. Understanding that effect requires accounting for the conditions affecting one's attention and experience. Rather than attempt to reduce and control environmental factors, we compare two similar groups during naturally occurring, intense and overwhelming conditions and examine the relationship between common characteristics as well as environment and group differences. Participants undertook a 5-day, winter, wilderness adventur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
0
16
0
11
Order By: Relevance
“…It is characterized by a period in which people restrict their social relations and impose limits on their movement [7,8], changing habits. These changes may be influenced by home conditions [9,10], which can also affect people's psychological well-being (PWB) [11,12]. The current technological development makes a big difference between the closure of COVID-19 and the previous isolation times.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by a period in which people restrict their social relations and impose limits on their movement [7,8], changing habits. These changes may be influenced by home conditions [9,10], which can also affect people's psychological well-being (PWB) [11,12]. The current technological development makes a big difference between the closure of COVID-19 and the previous isolation times.…”
Section: Introductionmentioning
confidence: 99%
“…Some types of Nature seem to stimulate biophilia and are preferred, while other types of Nature seem to stimulate biophobia and are avoided (for more details, see Kaplan and Kaplan, 1989 ). In general, people seem to become more fascinated by the kind of Nature that matches their feeling of affiliation ( Fredman and Emmelin, 2001 ; Van den Berg and Koole, 2006 ; Nisbet and Zelenski, 2011 ); thus, people who have a high affiliation with Nature prefer wilder natural environments ( Berto et al, 2018 ; Løvoll et al, 2020 ), while people with a lower affiliation tend to prefer more domestic natural environments ( Bixler and Floyd, 1997 ; Davis and Gatersleben, 2013 ).…”
Section: Biophilia As An Evolutionary Adaptationmentioning
confidence: 99%
“…In the context of wilderness therapy, Nicholls [4] did not intend to focus on the role of the specific landscape environment, yet found its impact to be pervasive and extensive for the health-related outcomes of the participants. While some studies explicitly mention that some landscape, such as blue space, may hold more restorative potential than others [32], other studies point out that the aesthetic experiences elicited by wilderness landscapes are vital to an impact on well-being [70,71]. Interestingly, Richardson et al [72] reported that aesthetic nature experiences also occur in urban environmental settings.…”
Section: The Importance Of Context Factors For the Facilitation Of Solo Experiencesmentioning
confidence: 99%